Application of multifunctional small molecule fluorescent probe BODIPY in life science. (December 2022) - Yuan, Lin; Su, Yingbin; Cong, Hailin; Yu, Bing; Shen, Youqing
Abstract: BODIPY and its derivative multifunctional small molecule probes have become the darlings in the field of biomedical materials due to its unique molecular structure, high brightness, and effective anti-tumor effects. The derivatives formed by BODIPY and metal or metal ions can not only regulate their molecular structure to make their optical properties highly sensitive, but also solve the autotoxicity problem of metal drugs in tumor treatment; The derivatives formed by the combination of BODIPY with other molecules also provide more molecular feasible choices for the development of integrated diagnosis and treatment. This review focuses on the latest research achievements of BODIPY derivatives in recent years, to be more precise, the imaging and photodynamic therapeutic effects of BODIPY derivatives in aqueous solution or cells. Graphical abstract: Application of BODIPY as fluorescent probe in tumor therapy, ion detection, amino acid monitoring and optical imaging. Image 1 Highlights: This paper reviews the unique anti-tumor mechanism of BODIPY derivatives. This paper reviews the BODIPY derivatives as fluorophores. This paper reviews the great advantages of BODIPY derivatives in the field of optical imaging. The development trend of multifunctional small molecule BODIPY has been prospected.